Kedudukan Hukum Salinan Akta Notaris dari Minuta Akta yang Belum Lengkap dalam Perspektif Prinsip Kehati-hatian - Ayu Purnama sari (Recital Review, 2022)
This study aims to analyze the position of the copy of the deed and the minutes of deed according to the precautionary principle and to find out the legal implications of the copy of the deed from the incomplete deed from the perspective of the precautionary principle. The formulation of the problem in this research is how the position of the copy of the deed and the minutes of the deed according to the precautionary principle and what are the legal implications of the copy of the deed from the incomplete deed from the perspective of the precautionary principle. The research's approaching method that will be used in this research is normative juridical based on the ambiguity of legal norms contained in Law No. 2 of 2014 concerning the position of a notary, Article 16 paragraph (1) letter a. This type of research data is secondary data consisting of primary, secondary, and tertiary legal materials. The data sources were then analyzed qualitatively. Based on the results of the study, it can be concluded that the position of the copy of the deed and the minutes of the deed according to the precautionary principle can be used as perfect evidence if the process of making the deed meets the formal and material requirements of the authentic deed and the procedures for making the deed as stipulated in the Notary Position Act. The legal implication of a deed copy of an incomplete deed from the perspective of the precautionary principle is that the deed has been degraded, in which it becomes a private deed and is null and void. It is recommended that the Notary in carrying out his duties must always apply the precautionary principle in every deed he makes. Thoroughly examine and observe  every statement, data, document, and letter used as the basis for making the deed, even though the notary has no obligation to ensure the authenticity of all of these things.